Preparing for the Second Accession Round after Copenhagen – What Lessons Can Be Learned from the First Round of Negotiations? - Pjer Simunovic (Romanian Journal of European Affairs, 2002)
As the title reveals it too, the article tries to deal with the enlargement process that the European Union is facing nowadays. The author focuses on the lessons that can be learned from the “First Round of Negotiations”, as these are of great importance for the countries that will not enter in the “Copenhagen Round” – Bulgaria and Romania, which have not yet been able to conclude the negotiations, Turkey, an “official candidate” but with whom the negotiations still have to begin and the “Stabilisation and Association Process” countries – Albania, Bosnia-Herzegovina, Croatia, Macedonia and Serbia-Montenegro. Taking into account that this is a less homogenous group than the “Copenhagen Round” group (in terms of their overall political, economic and social shape), the EU has to tackle with particular attention the future Rounds and to learn from the experience of the “Copenhagen Round”.